Analysis of The Development Cashless Transaction on The Need for Money Paper Based - Agung Joni Saputra; Ibnu Harris (Conference Series, 2020)
This study discusses the Analysis of Cashless Development of Cash Needs. This study aims to see the extent of the readiness of the people in Batam for the use of non-cash transactions (debit / credit cards, emoney, etc.), as well as see whether the community is ready to no longer use paper-based money. This research method is qualitative (primary) or by distributing questionnaires with a total of 400 respondents in Batam and some data from information obtained from news and Bank Indonesia. The results of this study are people in Batam are still not ready yet to no longer use paper money due to internet facility factors that have not reached every region, not to mention because people are accustomed to using paper money, and public knowledge is still minimal in the use of non-cash transactions. The people of Batam prefer to reduce the production of paper based money by Bank Indonesia but do not eliminate the paper-based money because not all regions or transactions can use non-cash transaction facilities.